The Immediate Effect of Hanging Exercise and Muscle Cylinder Exercise on the Angle of Trunk Rotation in Adolescent Idiopathic Scoliosis - Akçay, Burçin; Çolak, Tuğba Kuru; APTİ, ADNAN; Çolak, İlker (MDPI, 2024)
(1) Background: Semi-hanging and muscle cylinder exercises have been defined as scoliosis-specific corrective exercises. The aim of this study was to evaluate the immediate effect of muscle cylinder and semi-hanging exercises on the angle of trunk rotation in patients with adolescent idiopathic scoliosis (AIS). (2) Methods: Twenty-seven patients with AIS with a mean age of 18.6 years were retrospectively analyzed. The angle of trunk rotation (ATR) values were measured before and after performing semi-hanging and standing muscle cylinder exercises. Both exercises were performed for three to five respiratory cycles. The semi-hanging exercise was performed first, followed by the muscle cylinder exercise, in this order, in all participants. For statistical analysis, the Wilcoxon signed-rank test was used to analyze ATR changes after the exercises, and the Kruskal-Wallis test was used to compare ATR changes according to the main curve location. (3) Results: The thoracic, thoracolumbar and lumbar maximum ATR values were significantly increased after the semi-hanging exercise (p < 0.001) and decreased after the muscle cylinder exercise (p < 0.001). The ATR change was greater in the lumbar region than in the thoracic and thoracolumbar regions. (4) Conclusion: The results of this study of a small group of patients emphasized that one of the scoliosis-specific corrective exercises, the standing muscle cylinder exercise, improved ATR, while the other, the semi-hanging exercise, worsened ATR in patients with AIS. It is recommended that each scoliosis-specific corrective exercise be evaluated and redesigned to maximize the three-dimensional corrective effect, considering the biomechanics of the spine and the pathomechanics of scoliosis.
Keywords: Adolescent Idiopathic Scoliosis; Angle of Trunk Rotation; Schroth; Scoliosis-specific Exercises